Adaptation Of Words In The Kashkadaryo Dialects (Global Scientific Review, 2025)
Any language is in a process of constant development and change. Fromthis perspective, dialects, as living forms of language, also go through their own stagesof development. Dialects of the Uzbek language have their own phonetic, lexical, andmorphological characteristics in different regions. In particular, the dialects observedamong the population living in the Kashkadarya region have a rich history and acomplex linguistic system, and the assimilations in this region, that is, words that havecome from other languages and their methods of formation, are one of the issues thatdeserve separate study. This article analyzes how words that have come from otherlanguages are formed in the Uzbek dialects of the Kashkadarya region, the cases inwhich they have undergone phonetic, morphological, and semantic changes, and whatlanguage units participated in these processes.